The Atlantic salmon : genetics, conservation and management - Verspoor, Eric.; Stradmeyer, L.; Nielsen, Jennifer L. (Blackwell Pub., 2007)
Atlantic Salmon is a cultural icon throughout its North Atlantic range; it is the focus of probably the World"s highest profile recreational fishery and is the basis for one of the World"s largest aquaculture industries. Despite this, many wild stocks of salmon are in decline and underpinning this is a dearth of information on the nature and extent of population structuring and adaptive population differentiation, and its implications for species conservation. This important new book will go a long way to rectify this situation by providing a thorough review of the genetics of Atlantic salmon. Sponsored by the European Union and the Atlantic Salmon Trust, this book comprises the work of an international team of scientists, carefully integrated and edited to provide a landmark book of vital interest to all those working with Atlantic salmon.